Runaway romances : Hollywood's postwar tour of Europe - Shandley, Robert R. (Temple Univ. Press, 2009)
Examines Hollywood's European travelogue romances from 1947 to 1964, the end of American isolationism and the advent of challenges in Hollywood that made American filmmakers begin filming abroad.